Ieiwsks,s,s,d d smsmslww
Lsleeldldd
one way is to solve for the invers of the first function
remembe, to solve, replace f(x) or g(x) with y, switch x and y, solve for y and replace it with f⁻¹(x)
A.
f(x)=x/2+8
y=x/2+8
x=y/2+8
x-8=y/2
2x-16=y
f⁻¹(x)=2x-16
nope, not A
B.
f(x)=3x³+16
y=3x³+16
x=3y³+16
x-16=3y³
(x-16)/3=y³
∛((x-16)/3)=y
f⁻¹(x)=∛((x-16)/3)
nope, not the same
not B
C.
f(x)=18/x-9
y=18/x-9
x=18/y-9
x+9=18/y
y(x+9)=18
y=18/(x+9)
f⁻¹(x)=18/(x+9)
correct, the answer is C
answer is C
Step-by-step explanation:
3/4 + 1/2= 3+2/4= 5/4
Hope it helps you
Answer:
problem 1 2x+5y= 0
×=-1/2-5/2y
problem 2 y=1 3/7y y=-1.428571
7y=-10
problem 3 x=-7
problem 4 x-y=20
x=-20